Interaction of Adenosine, Modified Using Carborane Clusters, with Ovarian Cancer Cells: A New Anticancer Approach against Chemoresistance - Bednarska-Szczepaniak, Katarzyna; Przelazły, Ewelina; Kania, Katarzyna Dominika; Szwed, Marzena; Litecká, Miroslava; Grűner, Bohumír; Leśnikowski, Zbigniew J (Cancers, 2021)
Platinum compounds remain the first-line drugs for the treatment of most lethal gynecological malignancies and ovarian cancers. Acquired platinum resistance remains a major challenge in gynecological oncology. Considering the unique physicochemical properties of the metallacarboranes modifier and the significant role of nucleoside derivatives as anticancer antimetabolites, we designed and synthesized a set of adenosine conjugates with metallacarboranes containing iron, cobalt, or chromium as semi-abiotic compounds that influence the cisplatin sensitivity of ovarian cancer cells. Adherent cultures of ovarian carcinoma cell lines and multicellular spheroids, ranging from sensitive to highly resistant including experimental cell lines "not responding" to platinum drugs were used. Iron-containing metallacarborane conjugates showed the best anticancer activity, especially against resistant cells. Compound modified at the C2' nucleoside position showed the best activity in resistant cancer cells and highly resistant cancer spheroids exposed to cisplatin, increasing cell cycle arrest, apoptosis or necrosis, and reactive oxygen species production. Moreover, it showed high cellular accumulation and did not induce cross-resistance to cisplatin, carboplatin, doxorubicin, paclitaxel, or gemcitabine in long-term cultures. The reference nido-carborane derivative (no metal ions) and unmodified nucleosides were not as effective. These findings indicate that metallacarborane modification of adenosine may sensitize ovarian cancer cells to cisplatin in combination treatment.
Keywords: reactive oxygen species; chemoresistance; ovarian cancer; cancer spheroids; metallacarboranes; nucleoside derivatives; apoptosis; cisplatin